Tawhid sebagai Prinsip Primordial Peradaban Islam: Studi Pemikiran Isma’il Raji al-Faruqi - Fadhil Sofian Hadi (TSAQAFAH, 2019)
Abstract Ismail Raji al-Faruqi is known as a contemporary Muslim scholar who played an important role and instigator the idea of the Islamization of contemporary science. To realize the idea of the Islamization of contemporary science, al-Faruqi sparked the founding of the International of Islamic Thought (IIIT) centered in the United States. Al-Faruqi is not only well known for his ideas in the arena of thought but also authored a book titled “Al-Tawḥîd: Its Implications for Thought and Life". In this book al-Faruqi describes the principle of tawhîd as the principle of the revival of the ummah. However, this principle began to be eroded and shaken by the understanding of a secular-liberal modern society. For al-Faruqi, the concept of tawḥîd is a primordial element as the true identity of civilization. Bearing in mind the identity of civilization, tawḥîd must be understood as a universal concept that is able to make a major contribution to the revival of Islamic civilization in the past. There are thirteen principles of tauhîd explained by al-Faruqi. All of these principles are inherently interrelated to one another. In connection with the writing of this paper, the author focuses his analysis and discussion on four main principles with the assumption that allows a deeper study. The four principles that the writer will describe are; first the principle of tawḥîd as a worldview. Second, tawḥîd as the principle of knowledge. Third, tawḥîd as a family principle that means the family in Islam has a support that is Islamic law which is determined by tawḥîd and Islamic religious experience. Fourth, tawḥîd as a metaphysical principle. This paper tries to explore the ideas of al-Faruqi in the frame of the analysis of the interrelation of the four principles in an effort to refresh the detention of Muslims in the path of realizing Islamic civilization. Keywords: Tawhid, Ismail Raji al-Faruqi, Islam, Knowledge, Civilization. AbstrakIsmail Raji al-Faruqi dikenal sebagai cendekiawan Muslim kontemporer yang berperan besar dalam menggagas ide Islamisasi Ilmu pengetahuan kontemporer. Untuk merealisasikan gagasan Islamisasi Ilmu Pengetahuan kontemporer, al-Faruqi mencetus berdirinya International of Islamic Thought (IIIT) berpusat di Amerika Serikat. Tidak hanya itu, al-Faruqi juga mengarang sebuah buku dengan judul “Al-Tawhîd: Its Implications for Thought and Life”. Di dalam buku tersebut al-Faruqi mengurai prinsip tawḥîd sebagi asas kebangkitan ummah. Namun prinsip tersebut mulai tergerus dan tergoyah oleh paham masyarakat modern yang sekuler-liberal. Bagi al-Faruqi, konsep tawḥîd merupakan unsur primordial sebagai identitas peradaban yang sebenarnya. Mengingat sebagai identitas peradaban, maka tawḥîd harus dipahami sebagai konsep universal yang mampu memberikan kontribusi besar bagi tegaknya kembali peradaban Islam masa silam. Terdapat tiga belas prinsip tawḥîd yang dipaparkan al-Faruqi. Semua prinsip tersebut adalah inheren saling terkait satu sama lain. Kaitannya dengan penulisan makalah ini, penulis memfokuskan analisa dan pembahasan pada empat prinsip pokok dengan asumsi memungkinkan dilakukan kajian lebih mendalam. Keempat prinsip yang akan penulis urai ialah, pertama prinsip tawḥîd sebagai pandangan dunia (worldview). Kedua, tawḥîd sebagai prinsip pengetahuan. Ketiga, tawḥîd sebagai prinsip keluarga yang bermakna keluarga dalam Islam mempunyai penopang yaitu hukum Islam yang dideterminasi oleh tawḥîd dan pengalaman agama Islam. Keempat, tawḥîd sebagai prinsip metafisika. Makalah ini mencoba mengupas gagasan al-Faruqi dalam bingkai analisis keterkaitan empat prinsip tersebut dalam upaya menyegarkan pemahanan kaum Muslimin dalam meniti jalan mewujudkan kembali peradaban Islam. Kata Kunci: Tawhîd, Ismail Raji al-Faruqi, Islam, Pengetahuan, Peradaban.